Sekundarna amiloidoza ob Crohnovi bolezni ter nefrotični sindrom: prikaz primera - Ekart, Robert (Zdravniški vestnik, 2004)
Background. Amyloidosis is a group of diseases, for which the extracellular deposition of fibrillary protein, called amyloid, is typical. There are many kinds of amyloidoses. Secondary amyloidosis is connected with previously existing inflammatory disorders which also include the Crohn's disease. The kidneys are important target organs. Proteinuria is usually the first sign of deposition of the amyloid in the kidneys. The nephrotic syndrome is important for the prognosis of the disease. The treatment of the secondary amyloidosis is limited to colhicin therapy and treatment of basic inflammatory process and its complications. Patients and methods. The 67 years old female was accepted in hospital because of uncontrolled high blood pressure, microcyte anemia, high levels of serum creatinine and urea. Nephrotic syndrome was present. Kidney biopsy showed a secondary amyloidosis. Colonoscopy showed the signs of Crohn's disease of rectosigma. The patient was treated with antihypertonic therapy, hydrocortisone enemas and mesalazine. Conclusions. A rare form of secondary amyloidosis connected with Crohn's disease was presented that had caused the nephrotic syndrome and renal failure.
Keywords: Amiloidoza; Amyloidosis; Crohn disease; Crohnova bolezen; Nefrotični sindrom; Nephrotic syndrome; Proteinuria; Proteinurija